Silicon carbide composite seed crystal and method of making same, silicon carbide crystal
Patent Information
- Application Number
- CN202510535578.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-27
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2045-04-27
AI Technical Summary
[0005]本申请的目的在于提供碳化硅复合籽晶的制备方法,用于解决碳化硅材料的低热导率不利于形成碳化硅晶体所需要的在垂直方向大的温度梯度,因此碳化硅晶体的生长速度不仅慢,生长厚度也非常小,即碳化硅晶体长不厚,厚度一般仅为20~25mm,或者在长厚的情况下晶体内部质量差,无法得到电子级的碳化硅晶体的问题;通过本申请方法制备的碳化硅复合籽晶在实现大直径、高厚度、低成本的碳化硅晶体的生长的同时,还能保证碳化硅晶体的生长质量
[0013]通过在低热导率的碳化硅籽晶的表面上形成高热导率的碳化硅过渡层,使碳化硅籽晶的硅面与碳化硅过渡层的硅面通过硅原子扩散结合,降低了界面应力,增强了两相的结合强度;通过在高热导率的碳化硅过渡层的碳面上形成更高热导率的金刚石层,使碳化硅过渡层作为热应力缓冲层,减少因碳化硅籽晶与金刚石层之间的热膨胀系数差异而导致的界面裂纹或剥离。
Smart Images

Figure CN120401008B_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of semiconductor material preparation, and in particular to silicon carbide composite seed crystals and their preparation methods, as well as silicon carbide crystals including the silicon carbide composite seed crystals. Background Technology
[0002] Silicon carbide single crystals are generally produced as large-size bulk crystals for commercial applications through PVT (Physical Vapor Transport) and LPE (Liquid Phase Epitaph), but the growth rate is much lower than that of silicon crystals.
[0003] The slow growth rate of silicon carbide crystals is due to the poor physical properties of the silicon carbide single-crystal seed crystals used in both physical vapor deposition (PVD) and flux-fluid liquid phase (CFLP) methods. Traditional seed crystals consist of silicon carbide single-crystal material of a certain thickness. The thermal conductivity of silicon carbide single-crystal material is only 490 W / (m·K). Factors affecting the thermal conductivity of silicon carbide single-crystals include impurities and crystal structure defects. During crystal growth, the temperature gradient is the intrinsic driving force for single-crystal crystallization and a key factor determining the crystal growth rate. The crystal growth rate is closely and positively correlated with the temperature gradient; a larger temperature gradient results in a faster crystallization rate, and vice versa. The low thermal conductivity of silicon carbide material is unfavorable for forming the large temperature gradient required in the vertical direction for silicon carbide crystals. Therefore, the growth rate of silicon carbide crystals is not only slow, but the growth thickness is also very small, meaning the silicon carbide crystals are not thick (generally only 20-25 mm), or, if they are thick, the internal quality of the crystal is poor, making it impossible to obtain electronic-grade silicon carbide crystals.
[0004] This application addresses at least one of the aforementioned problems. Summary of the Invention
[0005] The purpose of this application is to provide a method for preparing silicon carbide composite seed crystals, which solves the problem that the low thermal conductivity of silicon carbide material is not conducive to the formation of silicon carbide crystals, which requires a large temperature gradient in the vertical direction. As a result, the growth rate of silicon carbide crystals is not only slow, but the growth thickness is also very small. That is, the silicon carbide crystals are not thick, and the thickness is generally only 20-25 mm. Or, if they are thick, the internal quality of the crystal is poor, and it is impossible to obtain electronic-grade silicon carbide crystals. The silicon carbide composite seed crystals prepared by the method of this application can achieve the growth of large-diameter, high-thickness, and low-cost silicon carbide crystals, while also ensuring the growth quality of silicon carbide crystals.
[0006] To achieve the above objectives, this application adopts the following technical solution:
[0007] In a first aspect, the present invention provides a method for preparing silicon carbide composite seed crystals, comprising the following steps:
[0008] Provide silicon carbide seed crystals;
[0009] A silicon carbide transition layer is formed on the silicon surface of the silicon carbide seed crystal, and the carbon surface of the silicon carbide transition layer is moved away from the silicon surface of the silicon carbide seed crystal to obtain a silicon carbide composite structure.
[0010] A diamond layer is formed on the carbon surface of the silicon carbide transition layer to obtain a silicon carbide composite seed crystal;
[0011] The thermal conductivity of the silicon carbide transition layer is less than that of the diamond layer, and the thermal conductivity of the silicon carbide transition layer is greater than that of the silicon carbide seed crystal; the crystal form of the silicon carbide transition layer is different from that of the silicon carbide seed crystal.
[0012] Compared with the prior art, the beneficial effects of this application are as follows:
[0013] By forming a high thermal conductivity silicon carbide transition layer on the surface of a low thermal conductivity silicon carbide seed crystal, the silicon surface of the silicon carbide seed crystal and the silicon surface of the silicon carbide transition layer are bonded through silicon atom diffusion, which reduces interfacial stress and enhances the bonding strength between the two phases. By forming a diamond layer with even higher thermal conductivity on the carbon surface of the high thermal conductivity silicon carbide transition layer, the silicon carbide transition layer acts as a thermal stress buffer layer, reducing interfacial cracks or peeling caused by the difference in thermal expansion coefficients between the silicon carbide seed crystal and the diamond layer.
[0014] By establishing a temperature gradient between a low thermal conductivity silicon carbide seed crystal, a high thermal conductivity silicon carbide transition layer, and an even higher thermal conductivity diamond layer, heat at the silicon carbide seed crystal can be rapidly transferred out along both the vertical and horizontal directions. This allows the silicon carbide composite seed crystal to achieve a large temperature gradient in both directions, which not only increases the growth rate of silicon carbide crystals in the vertical direction, facilitating the growth of silicon carbide crystals with a thickness of 50 mm or more, but also increases the growth rate of silicon carbide crystals in the horizontal direction, promoting diameter expansion during crystal growth and facilitating the growth of large-diameter silicon carbide crystals. This significantly reduces the growth cost of silicon carbide materials. In summary, the silicon carbide composite seed crystal prepared using the above method can achieve the growth of large-diameter, high-thickness, and low-cost silicon carbide crystals while ensuring the growth quality of silicon carbide crystals.
[0015] In some possible embodiments of the first aspect, during the formation of the silicon carbide transition layer on the silicon surface of the silicon carbide seed, the silicon surface of the silicon carbide seed and the silicon surface of the silicon carbide transition layer are bonded by silicon atom diffusion; the formation of the silicon carbide transition layer on the silicon surface of the silicon carbide seed includes:
[0016] Under conditions of temperature of 850–900℃, gas pressure of 20–30 kPa, flow rates of SiH4 and CH4 of 2–20 sccm, and flow rate of H2 of 200–500 sccm, an initial silicon carbide transition layer of 50–200 μm thickness is prepared by chemical vapor deposition on the silicon surface of the silicon carbide seed crystal with a thickness of 100–200 μm for 10–20 h.
[0017] The carbon surface of the initial silicon carbide transition layer is ground and polished to obtain a silicon carbide transition layer with a thickness of 10-50 μm and a surface roughness less than the first preset roughness.
[0018] The value range of the first preset roughness is 1 to 5 nm.
[0019] In some possible embodiments of the first aspect, during the formation of the silicon carbide transition layer on the silicon surface of the silicon carbide seed, the silicon surface of the silicon carbide seed and the silicon surface of the silicon carbide transition layer are bonded by silicon atom diffusion; the formation of the silicon carbide transition layer on the silicon surface of the silicon carbide seed includes:
[0020] Under conditions of temperature of 1900–2100℃ and pressure of 0.001–0.03 Pa, the silicon surface of a silicon carbide seed crystal with a thickness of 100–200 μm is heterobonded to the silicon surface of the initial silicon carbide transition layer to obtain the first heterobonded structure.
[0021] Wherein, the surface roughness of the silicon surface of the initial silicon carbide transition layer is less than the second preset roughness, and the value range of the second preset roughness is 1 to 5 nm;
[0022] After heterobonding is completed, the first heterobonded structure is annealed for 20 to 40 hours at an annealing temperature of 1800 to 1900°C and an annealing atmosphere of argon or nitrogen, so that the initial silicon carbide transition layer is transformed into the silicon carbide transition layer.
[0023] The thickness of the silicon carbide transition layer is 10–50 μm.
[0024] In some possible embodiments of the first aspect, during the formation of a diamond layer on the carbon facet of the silicon carbide transition layer, the carbon facet of the silicon carbide transition layer and the surface of the diamond layer are bonded together by carbon atom diffusion; the formation of a diamond layer on the carbon facet of the silicon carbide transition layer includes:
[0025] An initial diamond layer with a thickness of 500-900 μm was grown on the carbon surface of the silicon carbide transition layer using chemical vapor deposition.
[0026] The initial diamond layer is ground and polished to obtain a diamond layer with a thickness of 300-500 μm and a surface roughness less than a third preset roughness;
[0027] The value range of the third preset roughness is 1 to 5 nm.
[0028] In some possible embodiments of the first aspect, the growth of an initial diamond layer with a thickness of 500-900 μm on the carbon surface of the silicon carbide transition layer comprises:
[0029] Under conditions of temperature of 850–900℃, pressure of 20–30 kPa, flow rate of CH4 of 2–20 sccm, flow rate of H2 of 200–500 sccm, and flow rate of O2 of 2–20 sccm, MPCVD was used to grow the carbon surface of the silicon carbide transition layer for 60–90 h to prepare the initial diamond layer with a thickness of 500–900 μm.
[0030] Alternatively, under conditions of a temperature of 2200–2300 °C, a gas pressure of 20–30 kPa, a CH4 flow rate of 2–20 sccm, and an H2 flow rate of 200–500 sccm, HFCVD is used to grow the carbon surface of the silicon carbide transition layer for 60–90 h to prepare the initial diamond layer with a thickness of 500–900 μm.
[0031] Alternatively, under conditions of 850–900 °C, 20–30 kPa, CH4 flow rate of 2–20 sccm, and H2 flow rate of 200–500 sccm, DCPCVD is used to grow the initial diamond layer with a thickness of 500–900 μm on the carbon surface of the silicon carbide transition layer for 5–10 h.
[0032] In some possible embodiments of the first aspect, during the formation of a diamond layer on the carbon facet of the silicon carbide transition layer, the carbon facet of the silicon carbide transition layer and the surface of the diamond layer are bonded together by carbon atom diffusion; the formation of a diamond layer on the carbon facet of the silicon carbide transition layer includes:
[0033] Under conditions of temperature of 1900–2100℃ and pressure of 0.001–0.03 Pa, the carbon surface of the silicon carbide transition layer is heterogeneously bonded to the surface of the initial diamond layer to obtain a second heterogeneous bonding structure.
[0034] Wherein, the surface roughness of the initial diamond layer is less than the fourth preset roughness, and the value of the fourth preset roughness ranges from 1 to 5 nm;
[0035] After heterobonding is completed, the second heterobonded structure is annealed for 20 to 40 hours at an annealing temperature of 1800 to 1900°C and an annealing atmosphere of argon or nitrogen, so that the initial diamond layer is transformed into the diamond layer.
[0036] The thickness of the diamond layer is 300-500 μm.
[0037] In some possible embodiments of the first aspect, prior to forming the diamond layer, the preparation method further includes: forming a plurality of first microchannels in the form of protrusions or grooves on the carbon surface of the silicon carbide transition layer;
[0038] And / or, before heterobonding the carbon surface of the silicon carbide transition layer to the surface of the initial diamond layer, the method further includes: forming a plurality of second microchannels in the form of protrusions or grooves on the surface of the initial diamond layer;
[0039] The first microchannel with a protrusion corresponds to the second microchannel with a groove, so that the first microchannel with a protrusion can be embedded in the second microchannel with a groove; the second microchannel with a protrusion corresponds to the first microchannel with a groove, so that the second microchannel with a protrusion can be embedded in the first microchannel with a groove.
[0040] In some possible embodiments of the first aspect, the formation of a plurality of first microchannels in the form of protrusions or grooves on the carbon surface of the silicon carbide transition layer includes:
[0041] Under conditions of pulse width of 500ps to 1ns, laser power of 10 to 15W, and laser repetition frequency of 20 to 100kHz, laser etching is used to form multiple first microchannels in the carbon surface of the silicon carbide transition layer in the form of protrusions or grooves; or under conditions of etching temperature exceeding 1800℃ and etching gas of CF4, O2, or Ar, plasma etching is used to form multiple first microchannels in the carbon surface of the silicon carbide transition layer in the form of protrusions or grooves.
[0042] Wherein, the width of the first microchannel is 5-10 μm; and / or, the depth of the first microchannel is 30-50 μm; and / or, the lateral spacing of the first microchannel is 5-10 mm.
[0043] And / or, the formation of a plurality of second microchannels in the form of protrusions or grooves on the surface of the initial diamond layer includes:
[0044] Under conditions of pulse width of 500ps to 1ns, laser power of 10 to 15W, and laser repetition frequency of 20 to 100kHz, multiple second microchannels in the shape of protrusions or grooves are formed on the surface of the initial diamond layer by laser etching; or under conditions of etching temperature exceeding 1800℃ and etching gas of CF4, O2, or Ar, multiple second microchannels in the shape of protrusions or grooves are formed on the surface of the initial diamond layer by plasma etching.
[0045] Wherein, the width of the second microchannel is 5-10 μm; and / or, the depth of the second microchannel is 30-50 μm; and / or, the lateral spacing of the second microchannel is 5-10 mm.
[0046] And / or, the thickness of the diamond layer is less than or equal to two-thirds of the thickness of the silicon carbide composite seed crystal, and the thickness of the diamond layer is greater than or equal to one-half of the thickness of the silicon carbide composite seed crystal;
[0047] And / or, the thickness of the silicon carbide seed crystal is less than one-third of the thickness of the silicon carbide composite seed crystal.
[0048] In a second aspect, the present invention provides a silicon carbide composite seed crystal, which is prepared using the above-described method for preparing silicon carbide composite seed crystals.
[0049] In a third aspect, the present invention provides a silicon carbide crystal comprising the aforementioned silicon carbide composite seed crystal. Attached Figure Description
[0050] Figure 1 A flowchart illustrating the overall steps of the method for preparing silicon carbide composite seed crystals provided in this application;
[0051] Figure 2 This is a schematic diagram of the structure of the silicon carbide composite seed crystal provided in this application;
[0052] Figure 3 A schematic diagram of the first and second microchannels provided in this application, which are arranged in a vortex-shaped mosquito coil pattern.
[0053] In the figure, 10 is a silicon carbide composite seed crystal; 11 is a silicon carbide seed crystal; 12 is a silicon carbide transition layer; and 13 is a diamond layer. Detailed Implementation
[0054] Exemplary embodiments will now be described more fully with reference to the accompanying drawings. However, these exemplary embodiments can be implemented in many forms and should not be construed as limited to the embodiments set forth herein; rather, these embodiments are provided to make this application more complete and comprehensive, and to fully convey the concept of the exemplary embodiments to those skilled in the art. The same reference numerals in the drawings denote the same or similar structures, and therefore repeated descriptions of them will be omitted.
[0055] The terms used in this application to express position and direction are illustrated with the accompanying drawings, but may be changed as needed, and all such changes are included within the scope of protection of this application.
[0056] In a first aspect, this embodiment provides a method for preparing silicon carbide composite seed crystals, combined with... Figure 1 As shown, it includes the following steps S1-S3.
[0057] Step S1: Provide silicon carbide seed crystals.
[0058] The silicon carbide material in the silicon carbide seed crystal can be 3C, 4H, 6H or 15R crystal form, etc., and the preferred crystal form in this embodiment is 4H crystal form.
[0059] The thickness of the silicon carbide seed crystal is 100–200 μm, for example, it can be 100 μm, 120 μm, 150 μm, 180 μm or 200 μm; the diameter of the silicon carbide seed crystal matches the diameter of the silicon carbide crystal to be grown, generally 6–12 inches, for example, it can be 6 inches, 7 inches, 8 inches, 9 inches, 10 inches, 11 inches or 12 inches.
[0060] It should be noted that the thickness of the silicon carbide seed crystal is less than one-third the thickness of the silicon carbide composite seed crystal.
[0061] By controlling the thickness of the silicon carbide seed crystal within the above range, the overall thermal conductivity of the prepared silicon carbide composite seed crystal can be more than 40% higher than that of the pure silicon carbide seed crystal. The temperature gradient of the silicon carbide composite seed crystal increases by 15-20% in the vertical direction and by 10% in the horizontal direction.
[0062] Furthermore, as a preferred embodiment of this application, the preparation method further includes steps S11-S14 before forming the silicon carbide transition layer.
[0063] Step S11: Polish the surface of the silicon carbide seed crystal.
[0064] For example, a silicon carbide crystal of suitable size is cut from a high-quality silicon carbide single crystal material to serve as a silicon carbide seed crystal. The surface of the silicon carbide seed crystal is polished to make its silicon surface roughness less than a preset roughness, the preset roughness being 1 to 5 nm. For example, the surface roughness of the silicon surface of the silicon carbide seed crystal can be 0.5 nm, 1 nm, 2 nm, 3 nm, or 4 nm.
[0065] Furthermore, the silicon carbide seed crystal can be first ground with diamond polishing slurry to achieve high precision, and then the ground silicon carbide seed crystal can be chemically and mechanically polished.
[0066] Step S12: Acid washing is performed on the polished silicon carbide seed crystal.
[0067] For example, silicon carbide seed crystals can be pickled by soaking them in aqua regia (a mixture of nitric acid and hydrochloric acid) for 30 minutes to remove contaminant particles from the surface of the silicon carbide seed crystals.
[0068] Step S13: Perform ultrasonic cleaning on the acid-washed silicon carbide seed crystal.
[0069] For example, ultrasonic cleaning of silicon carbide seed crystals with acetone solution for 10 minutes can penetrate deep into the microporous structure of the silicon carbide seed crystal surface, achieving thorough cleaning without dead angles. This not only further removes contaminant particles and polishing reagent residues from the silicon carbide seed crystal surface, but also creates micro-scratches on the surface of the silicon carbide seed crystal, optimizing its surface morphology. This, in turn, increases the nucleation density and bonding force with the subsequent silicon carbide transition layer, allowing the nucleation density to reach up to 10. 9 / cm 2 .
[0070] Step S14: Dry the ultrasonically cleaned silicon carbide seed crystal. For example, bake the silicon carbide seed crystal in an oven at 200°C for 15 minutes to dry it.
[0071] Through the above steps, efficient decontamination of silicon carbide seed crystals is achieved, ensuring the integrity and high cleanliness of their surface. This reduces defects caused by contaminants during the subsequent formation of the silicon carbide transition layer, ensuring that the number of particles (0.3μm scale) on the surface of the silicon carbide seed crystal is less than 500-1000, thus ensuring the uniformity and adhesion of the silicon carbide transition layer on the surface of the silicon carbide seed crystal.
[0072] Step S2: A silicon carbide transition layer is formed on the silicon surface of the silicon carbide seed crystal, and the carbon surface of the silicon carbide transition layer is moved away from the silicon surface of the silicon carbide seed crystal to obtain a silicon carbide composite structure.
[0073] The silicon carbide transition layer is mainly composed of the (111) crystal plane; the thickness of the silicon carbide transition layer is 10 to 50 μm, for example, it can be 10 μm, 20 μm, 30 μm, 40 μm or 50 μm.
[0074] It should be noted that the thermal conductivity of the silicon carbide transition layer is greater than that of the silicon carbide seed crystal, and the crystal form of the silicon carbide transition layer is different from that of the silicon carbide seed crystal. For the silicon carbide transition layer, the silicon carbide material in the silicon carbide transition layer can be 3C, 4H, 6H or 15R crystal forms, etc., and in this embodiment, the 3C crystal form is preferred.
[0075] It should be further explained that during the formation of the silicon carbide transition layer on the silicon surface of the silicon carbide seed crystal, the silicon surface of the silicon carbide seed crystal and the silicon surface of the silicon carbide transition layer are bonded together through silicon atom diffusion. Since the silicon atoms of the silicon carbide seed crystal and the silicon atoms of the silicon carbide transition layer are bonded together by forming covalent bonds, there is no intermediate transition layer between them, making their bonding even tighter.
[0076] Furthermore, as a preferred embodiment of this application, forming a silicon carbide transition layer on the silicon surface of the silicon carbide seed crystal includes steps S21a-S22a.
[0077] Step S21a: Under the conditions of temperature 850-900℃, gas pressure 20-30Kpa, flow rates of SiH4 and CH4 of 2-20sccm and flow rate of H2 of 200-500sccm, a silicon carbide seed crystal with a thickness of 100-200μm is grown on the silicon surface for 10-20 hours by chemical vapor deposition to prepare an initial silicon carbide transition layer with a thickness of 50-200μm.
[0078] For example, the thickness of the initial silicon carbide transition layer can be 50 μm, 70 μm, 90 μm, 110 μm, 130 μm, 150 μm, 170 μm, or 200 μm. The growth time of the initial silicon carbide transition layer can be 10 h, 12 h, 15 h, 18 h, or 20 h. The growth temperature of the initial silicon carbide transition layer can be 850℃, 860℃, 870℃, 880℃, 890℃, or 900℃; the gas pressure can be 20Kpa, 21Kpa, 22Kpa, 23Kpa, 24Kpa, 25Kpa, 26Kpa, 27Kpa, 28Kpa, 29Kpa, or 30Kpa; the flow rates of SiH4 and CH4 can both be 2sccm, 4sccm, 6sccm, 8sccm, 10sccm, 12sccm, 14sccm, 16sccm, 18sccm, or 20sccm; the flow rate of H2 can be 200sccm, 250sccm, 300sccm, 350sccm, 400sccm, 450sccm, or 500sccm; and the purity of SiH4, CH4, and H2 can be 99.9999%.
[0079] The inventors discovered that during the growth of the initial silicon carbide transition layer via chemical vapor deposition, growth is very slow if the temperature is below 850℃; while growth is faster if the temperature is above 900℃, the quality of the resulting initial silicon carbide transition layer is poor. If the pressure is below 20 kPa, the plasma power density is low, resulting in a slow growth rate; while if the pressure is above 30 kPa, the plasma density is high, leading to a faster growth rate, but also increasing the likelihood of amorphous carbides forming.
[0080] SiH4 and CH4 are the feed gases for chemical vapor deposition (CVD) growth of silicon carbide. If the concentration is too low (flow rate less than 2 sccm), the growth rate is very slow; if the concentration is too high (flow rate greater than 20 sccm), although the growth rate is fast, the quality of the grown silicon carbide material is very poor. Hydrogen is used as a carrier gas for the feed gases and can etch amorphous silicon carbide in a timely manner. If the concentration is too low (flow rate less than 200 sccm), the growth rate is very slow; if the concentration is too high (flow rate greater than 500 sccm), hydrogen will etch away other amorphous carbide materials.
[0081] If the growth time of the initial silicon carbide transition layer is too short (less than 10 hours), it is impossible to produce an initial silicon carbide transition layer of a certain thickness; if the growth time is too long (more than 20 hours), the quality of the initial silicon carbide transition layer will be low, which is not conducive to the preparation of silicon carbide composite seed crystals.
[0082] Step S22a: Grind and polish the carbon surface of the initial silicon carbide transition layer to obtain a silicon carbide transition layer with a thickness of 10-50 μm and a surface roughness less than the first preset roughness.
[0083] The first preset roughness ranges from 1 to 5 nm. For example, the surface roughness of the carbon surface of the silicon carbide transition layer can be 0.5 nm, 1 nm, 2 nm, 3 nm, or 4 nm.
[0084] Because the thermal conductivity of the silicon carbide transition layer in 3C-type silicon carbide material is 500 W / (m·K) higher than that of the silicon carbide seed crystal in 4H-type silicon carbide material (490 W / (m·K)), the high thermal conductivity silicon carbide transition layer can quickly conduct away the heat adsorbed by silicon and carbon atoms during the growth of silicon carbide crystals on the surface of silicon carbide seed crystals with low thermal conductivity, thereby establishing a larger temperature gradient in the vertical and horizontal directions in the silicon carbide composite seed crystal. At the same time, the silicon carbide transition layer can provide silicon atoms required for epitaxial growth of silicon carbide seed crystals and carbon atoms required for epitaxial growth of diamond layers, respectively, so that silicon carbide seed crystals and diamond layers can achieve a good epitaxial growth interface.
[0085] As another preferred embodiment of this application, forming a silicon carbide transition layer on the silicon surface of a silicon carbide seed crystal includes steps S21b-S22b.
[0086] Step S21b: Under the conditions of temperature of 1900~2100℃ and pressure of 0.001~0.03pa, the silicon surface of the silicon carbide seed crystal with a thickness of 100~200μm is heterobonded with the silicon surface of the initial silicon carbide transition layer to obtain the first heterobonded structure.
[0087] The surface roughness of the silicon surface of the initial silicon carbide transition layer is less than a second preset roughness, which ranges from 1 to 5 nm. For example, the surface roughness of the silicon surface of the initial silicon carbide transition layer can be 0.5 nm, 1 nm, 2 nm, 3 nm, or 4 nm.
[0088] For example, the temperature can be 1900℃, 1950℃, 2000℃, 2050℃ or 2100℃; the air pressure can be 0.001pa, 0.005pa, 0.01pa, 0.015pa, 0.02pa, 0.025pa or 0.03pa.
[0089] Through in-depth research, the inventors discovered that during heterogeneous bonding, if the temperature is below 1900℃, the bonding is weak and defects such as voids and microcracks are easily generated at the interface; if the temperature is above 2100℃, power consumption is excessive and it has little effect on improving the bonding strength. If the gas pressure is above 0.03Pa, the vacuum level is not high, and impurities such as air are easily introduced, affecting the bonding effect; if the gas pressure is below 0.001Pa, the requirements for system equipment are very high, resulting in high costs. Therefore, it is necessary to control the temperature and gas pressure of heterogeneous bonding within the above-mentioned ranges.
[0090] Under the above conditions, heterogeneous bonding (with all bonding surfaces being silicon surfaces) is carried out. The initial silicon carbide transition layer and the silicon carbide seed crystal have a small lattice mismatch and a very low solid-solid interface energy, making it easy to achieve silicon carbide bonding without an intermediate layer. This not only promotes the formation of chemical bonds between the two and reduces the interface defect density, but also allows the surfaces of the two to be in close contact, reducing micropores and gaps, thereby improving the compactness and mechanical strength of the first heterogeneous bonding structure.
[0091] Furthermore, it can reduce the residual stress at the interface caused by the difference in thermal expansion between the initial silicon carbide transition layer of the 3C-type silicon carbide material and the silicon carbide seed crystal of the 4H-type silicon carbide material, thus preventing cracking of the first heterobonded structure. In addition, under these conditions, heterobonding results in low interfacial thermal resistance, and the high thermal conductivity of the silicon carbide transition layer can quickly conduct away the heat accumulated by the low thermal conductivity of the silicon carbide seed crystal, thereby establishing a larger temperature gradient in the vertical and horizontal directions within the silicon carbide composite seed crystal.
[0092] Step S22b: After heterobonding is completed, the first heterobonded structure is annealed for 20 to 40 hours at an annealing temperature of 1800 to 1900°C and an annealing atmosphere of argon or nitrogen, so that the initial silicon carbide transition layer is transformed into a silicon carbide transition layer.
[0093] The thickness of the silicon carbide transition layer is 10–50 μm, for example, it can be 10 μm, 20 μm, 30 μm, 40 μm or 50 μm. The annealing temperature can be 1800℃, 1820℃, 1850℃, 1880℃ or 1900℃; the annealing time can be 20h, 22h, 25h, 28h, 30h, 32h, 35h, 38h or 40h.
[0094] The inventors discovered that annealing below 1800℃, exceeding the aforementioned temperature range, results in poor removal of thermal stress and fails to effectively eliminate the thermal stress generated by bonding. Annealing at 1900℃ effectively removes internal thermal stress; further increases in temperature lead to high electricity costs and are not worthwhile. Similarly, the annealing time also needs to be controlled within the aforementioned range. Therefore, it is necessary to control the annealing temperature and time within the aforementioned range.
[0095] By annealing the first heterogeneous bonding structure under the above conditions, not only can the internal thermal stress generated during the bonding process be reduced, but the physical diffusion of silicon atoms can also be promoted at high temperature, thereby reducing the interfacial thermal resistance.
[0096] Furthermore, as a preferred embodiment of this application, the above preparation method further includes step S23 before forming the diamond layer.
[0097] Step S23: Form multiple first microchannels in the form of protrusions or grooves on the carbon surface of the silicon carbide transition layer.
[0098] As a preferred embodiment of step S23, step S23 includes: forming a plurality of first microchannels in the form of protrusions or grooves on the carbon surface of the silicon carbide transition layer by laser etching under the conditions of a pulse width of 500ps to 1ns, a laser power of 10 to 15W and a laser repetition frequency of 20 to 100kHz.
[0099] For example, the laser wavelength is 1064nm, 532nm, or 355nm; the pulse width is 500ps, 600ps, 700ps, 800ps, 900ps, or 1ns; the laser power is 10W, 11W, 12W, 13W, 14W, or 15W; and the laser repetition frequency is 20kHz, 30kHz, 40kHz, 50kHz, 60kHz, 70kHz, 80kHz, 90kHz, or 100kHz.
[0100] As another preferred embodiment of step S23, step S23 includes: forming a plurality of first microchannels in the form of protrusions or grooves on the carbon surface of the silicon carbide transition layer by plasma etching under the conditions of etching temperature exceeding 1800°C and etching gas being CF4, O2 or Ar.
[0101] For example, the etching temperature can be 1800°C, 1850°C, 1900°C, 2000°C or 2100°C.
[0102] For preferred options, please refer to the appendix. Figure 3 As shown, all the first microchannels are connected end to end and distributed in a vortex shape (mosquito coil pattern). The etching width of the first microchannel is 5-10 μm, for example, it can be 5 μm, 6 μm, 7 μm, 8 μm, 9 μm or 10 μm; the etching depth of the first microchannel is 30-50 μm, for example, it can be 30 μm, 35 μm, 40 μm, 45 μm or 50 μm; the lateral spacing of the first microchannel is 5-10 mm, for example, it can be 5 mm, 6 mm, 7 mm, 8 mm, 9 mm or 10 mm.
[0103] By setting up the first microchannel, the contact surface area between the silicon carbide transition layer and the diamond layer can be increased, thereby enhancing the heat transfer capacity of the silicon carbide transition layer and the diamond layer during the growth process, which helps to establish a larger temperature gradient in the vertical and horizontal directions for the silicon carbide composite seed crystal.
[0104] Step S3: A diamond layer is formed on the carbon surface of the silicon carbide transition layer to obtain a silicon carbide composite seed crystal.
[0105] The thermal conductivity of the silicon carbide transition layer is lower than that of the diamond layer; the thickness of the diamond layer is 300-500 μm, for example, it can be 300 μm, 350 μm, 400 μm, 450 μm or 500 μm.
[0106] It should be further noted that the thickness of the diamond layer is less than or equal to two-thirds of the thickness of the silicon carbide composite seed crystal, and the thickness of the diamond layer is greater than or equal to one-half of the thickness of the silicon carbide composite seed crystal.
[0107] By controlling the thickness of the diamond layer within the above range, the overall thermal conductivity of the prepared silicon carbide composite seed crystal is more than 40% higher than that of the pure silicon carbide seed crystal. The temperature gradient of the silicon carbide composite seed crystal can be increased by 15-20% in the vertical direction and by 10% in the horizontal direction.
[0108] This application does not have any particular limitation on the diamond layer; any suitable diamond layer in the art can be used to implement the technical solutions of this application. In some embodiments of this application, the diamond layer used can be selected from single-crystal diamond or polycrystalline diamond, preferably single-crystal diamond.
[0109] It should be further explained that during the formation of the diamond layer from the carbon face of the silicon carbide transition layer in the silicon carbide composite structure, the carbon face of the silicon carbide transition layer and the surface of the diamond layer are bonded together through carbon atom diffusion. Since the carbon atoms of the diamond layer and the carbon atoms of the silicon carbide transition layer are bonded through covalent bonds, there is no intermediate transition layer between them, resulting in a tighter bond.
[0110] Furthermore, as a preferred embodiment of this application, forming a diamond layer on the carbon surface of the silicon carbide transition layer includes steps S31a-S32a.
[0111] Step S31a: An initial diamond layer is grown on the carbon surface of the silicon carbide transition layer using chemical vapor deposition.
[0112] The initial diamond layer has a thickness of 500-900 μm. For example, the initial diamond layer thickness can be 500 μm, 550 μm, 600 μm, 650 μm, 700 μm, 750 μm, 800 μm, 850 μm or 900 μm.
[0113] As a preferred embodiment of step S31a, an initial diamond layer with a thickness of 500-900 μm is prepared by growing on the carbon surface of the silicon carbide transition layer for 60-90 hours under the conditions of temperature of 850-900℃, gas pressure of 20-30 kPa, CH4 flow rate of 2-20 sccm, H2 flow rate of 200-500 sccm, and O2 flow rate of 2-20 sccm.
[0114] For example, the temperature can be 850℃, 860℃, 870℃, 880℃, 890℃, or 900℃; the pressure can be 20Kpa, 21Kpa, 22Kpa, 23Kpa, 24Kpa, 25Kpa, 26Kpa, 27Kpa, 28Kpa, 29Kpa, or 30Kpa; and the CH4 flow rate can be 2sccm, 4sccm, 6sccm, 8sccm, 10sccm, 12sccm, 14sccm, 16sccm, 18sccm, or... 20 sccm; H2 flow rate can be 200 sccm, 250 sccm, 300 sccm, 350 sccm, 400 sccm, 450 sccm or 500 sccm; O2 flow rate can be 2 sccm, 4 sccm, 6 sccm, 8 sccm, 10 sccm, 12 sccm, 14 sccm, 16 sccm, 18 sccm or 20 sccm; growth time can be 60h, 65h, 70h, 75h, 80h, 85h or 90h.
[0115] The inventors discovered that during the MPCVD growth of the initial diamond layer, growth is very slow if the temperature is below 850℃; while growth is faster if the temperature is above 900℃, the quality of the resulting initial diamond layer is poor. If the gas pressure is below 20 kPa, the plasma power density is low, resulting in a slow growth rate; while if the gas pressure is above 30 kPa, the plasma density is high, leading to a faster growth rate, but the formation of non-diamond crystalline phases such as graphite or amorphous carbon is more likely.
[0116] CH4 is the feed gas for growing the initial diamond layer in MPCVD, providing the necessary carbon source for epitaxial growth. If the CH4 concentration is too low (flow rate less than 2 sccm), the growth rate is very slow; if the CH4 concentration is too high (flow rate greater than 20 sccm), although the growth rate is fast, the quality of the grown initial diamond layer is poor. H2 serves as the carrier gas for the feed gas, effectively etching not only non-diamond crystalline materials but also the grown diamond, thus improving the deposition quality and packing density of the initial diamond layer. If the H2 concentration is too low (flow rate less than 200 sccm), the growth rate is very slow; if the H2 concentration is too high (flow rate greater than 500 sccm), hydrogen will etch away both non-diamond crystalline materials and the grown diamond. O2 can increase the plasma power density, etching non-diamond phases (such as graphite or amorphous carbon), thereby improving the growth rate and quality of the initial diamond layer.
[0117] If the growth time of the initial diamond layer is too short (less than 60 hours), it is impossible to produce an initial diamond layer of a certain thickness; if the growth time is too long (more than 90 hours), the quality of the initial diamond layer will be low, which is not conducive to the preparation of the initial diamond layer.
[0118] As another preferred embodiment of step S31a, an initial diamond layer with a thickness of 500-900 μm is prepared by growing on the carbon surface of the silicon carbide transition layer for 60-90 hours under the conditions of a temperature of 2200-2300℃, a gas pressure of 20-30 kPa, a CH4 flow rate of 2-20 sccm, and an H2 flow rate of 200-500 sccm.
[0119] For example, the temperature can be 2200℃, 2220℃, 2240℃, 2260℃, 2280℃ or 2300℃; the gas pressure can be 20Kpa, 21Kpa, 22Kpa, 23Kpa, 24Kpa, 25Kpa, 26Kpa, 27Kpa, 28Kpa, 29Kpa or 30Kpa; the CH4 flow rate can be 2sccm, 4sccm, 6sccm, 8sccm, 10sccm, 12sccm, 14sccm, 16sccm, 18sccm or 20sccm; the H2 flow rate can be 200sccm, 250sccm, 300sccm, 350sccm, 400sccm, 450sccm or 500sccm; the growth time can be 60h, 65h, 70h, 75h, 80h, 85h or 90h.
[0120] The inventors discovered that during the growth of the initial diamond layer using HFCVD, growth is very slow if the temperature is below 2200℃; while growth is faster if the temperature is above 2300℃, the quality of the resulting initial diamond layer is poor. If the gas pressure is below 20 kPa, the plasma power density is low, resulting in a slow growth rate; while if the gas pressure is above 30 kPa, the plasma density is high, leading to a faster growth rate, but the formation of non-diamond crystalline phases such as graphite or amorphous carbon is more likely.
[0121] CH4 is the feed gas for the initial diamond layer grown by HFCVD, which can improve the carbon source required for the epitaxial growth of the initial diamond layer. If the concentration of CH4 is too low (flow rate less than 2 sccm), the growth rate is very slow; if the concentration of CH4 is too high (flow rate greater than 20 sccm), although the growth rate is fast, the quality of the grown initial diamond layer is very poor. H2 is the carrier gas for the feed gas. It can not only etch non-diamond crystalline materials in time, but also etch the grown diamond, which is beneficial to improving the deposition quality and packing density of the initial diamond layer. If the concentration of H2 is too low (flow rate less than 200 sccm), the growth rate is very slow; if the concentration of H2 is too high (flow rate greater than 500 sccm), hydrogen will not only etch away non-diamond crystalline materials, but also etch the grown diamond.
[0122] If the growth time of the initial diamond layer is too short (less than 60 hours), it is impossible to produce an initial diamond layer of a certain thickness; if the growth time is too long (more than 90 hours), the quality of the initial diamond layer will be low, which is not conducive to the preparation of the initial diamond layer.
[0123] HFCVD allows for the growth of polycrystalline diamond or single-crystal diamond of a certain thickness on a silicon carbide composite structure consisting of a silicon carbide seed crystal of 4H crystal form and a silicon carbide transition layer of 3C crystal form. As a thermally conductive material with high thermal conductivity, diamond can establish a large temperature gradient for the silicon carbide composite seed crystal during its growth, which helps to grow thicker and larger diameter silicon carbide crystals on the silicon carbide composite seed crystal.
[0124] As another preferred embodiment of step S31a, under the conditions of a temperature of 850-900℃, a gas pressure of 20-30Kpa, a CH4 flow rate of 2-20sccm, and an H2 flow rate of 200-500sccm, DCPCVD (Direct Current Plasma Chemical Vapor Deposition) is used to grow an initial diamond layer with a thickness of 500-900μm on the carbon surface of the silicon carbide transition layer for 5-10 hours to prepare the initial diamond layer with a thickness of 500-900μm.
[0125] For example, the temperature can be 850℃, 860℃, 870℃, 880℃, 890℃, or 900℃; the gas pressure can be 20Kpa, 21Kpa, 22Kpa, 23Kpa, 24Kpa, 25Kpa, 26Kpa, 27Kpa, 28Kpa, 29Kpa, or 30Kpa; the CH4 flow rate can be 2sccm, 4sccm, 6sccm, 8sccm, 10sccm, 12sccm, 14sccm, 16sccm, 18sccm, or 20sccm; the H2 flow rate can be 200sccm, 250sccm, 300sccm, 350sccm, 400sccm, 450sccm, or 500sccm; and the growth time can be 5h, 6h, 7h, 8h, 9h, or 10h.
[0126] The inventors discovered that during the growth of the initial diamond layer in DCPCVD, growth is very slow if the temperature is below 850℃; while growth is faster if the temperature is above 900℃, the quality of the resulting initial diamond layer is poor. If the pressure is below 20 kPa, the plasma power density is low, resulting in a slow growth rate; while if the pressure is above 30 kPa, the plasma density is high, leading to a faster growth rate, but the formation of non-diamond crystalline phases such as graphite or amorphous carbon is more likely.
[0127] CH4 is the feed gas for growing the initial diamond layer in DCPCVD. It provides the carbon source required for the epitaxial growth of the initial diamond layer. If the CH4 concentration is too low (flow rate less than 2 sccm), the growth rate is very slow; if the CH4 concentration is too high (flow rate greater than 20 sccm), although the growth rate is fast, the quality of the grown initial diamond layer is very poor. H2 is the carrier gas for the feed gas. It can not only etch non-diamond crystalline materials in time, but also etch the grown diamond, which is beneficial to improving the deposition quality and packing density of the initial diamond layer. If the H2 concentration is too low (flow rate less than 200 sccm), the growth rate is very slow; if the H2 concentration is too high (flow rate greater than 500 sccm), hydrogen will not only etch away non-diamond crystalline materials, but also etch the grown diamond.
[0128] If the growth time of the initial diamond layer is too short (less than 5 hours), it is impossible to produce an initial diamond layer of a certain thickness; if the growth time is too long (more than 10 hours), the quality of the initial diamond layer will be low, which is not conducive to the preparation of the initial diamond layer.
[0129] By utilizing DCPCVD, a certain thickness of polycrystalline diamond or single-crystal diamond material can be grown on a silicon carbide composite structure of silicon carbide seed crystal of 4H crystal type silicon carbide material and silicon carbide transition layer of 3C crystal type silicon carbide material. As a thermally conductive material with high thermal conductivity, diamond material can establish a large temperature gradient for silicon carbide composite seed crystal during the growth of silicon carbide crystal, which helps to grow thicker and larger diameter silicon carbide crystals on silicon carbide composite seed crystal.
[0130] Step S32a: Grind and polish the initial diamond layer to obtain a diamond layer with a thickness of 300-500 μm and a surface roughness less than the third preset roughness.
[0131] The third preset roughness ranges from 1 to 5 nm. For example, the surface roughness of the diamond layer can be 0.5 nm, 1 nm, 2 nm, 3 nm, or 4 nm.
[0132] Furthermore, the silicon carbide composite seed crystal can be first precision ground using diamond polishing slurry, and then chemically and mechanically polished to make the surface roughness of the diamond layer less than 1-5 nm. Post-processing of the silicon carbide composite seed crystal includes steps S33a-S35a.
[0133] Step S33a: Acid washing is performed on the polished silicon carbide composite seed crystal.
[0134] For example, silicon carbide composite seed crystals can be pickled by soaking them in aqua regia (a mixture of nitric acid and hydrochloric acid) for 30 minutes to remove contaminant particles from the surface of the silicon carbide composite seed crystals.
[0135] Step S34a: Perform ultrasonic cleaning on the acid-washed silicon carbide composite seed crystal.
[0136] For example, ultrasonic cleaning of silicon carbide composite seed crystals with acetone solution for 10 minutes can penetrate deep into the microporous structure of the silicon carbide composite seed crystal surface, achieving thorough cleaning without dead angles. This not only further removes contaminant particles and polishing reagent residues from the surface of the silicon carbide composite seed crystal, but also creates micro-scratches on the surface of the silicon carbide composite seed crystal, optimizing its surface morphology. This, in turn, improves the nucleation density and bonding force of the subsequently grown silicon carbide crystals, allowing the nucleation density to reach as high as 10⁹ / cm².
[0137] Step S35a: Dry the ultrasonically cleaned silicon carbide composite seed crystal.
[0138] For example, the silicon carbide composite seed crystal is dried by baking it in an oven at 200°C for 15 minutes.
[0139] Through the above steps, efficient decontamination of silicon carbide composite seed crystals is achieved, ensuring the integrity and high cleanliness of their surface. This reduces defects caused by contaminants during the subsequent formation of silicon carbide crystals, ensuring that the number of particles (0.3μm scale) on the surface of the silicon carbide composite seed crystal is less than 500-1000. This ensures the uniformity and adhesion of silicon carbide crystals on the surface of the silicon carbide composite seed crystal, making it suitable for use in various silicon carbide crystal growth methods.
[0140] The above scheme grows a silicon carbide transition layer and a diamond layer sequentially on a silicon carbide seed crystal using chemical vapor deposition. The resulting silicon carbide composite seed crystal has higher quality and reduces the dependence of pure silicon carbide seed crystals on high-quality silicon carbide single crystals in the prior art. It can be used to grow silicon carbide crystals with greater thickness and larger diameter.
[0141] As another preferred embodiment of this application, forming a diamond layer on the carbon surface of the silicon carbide transition layer includes steps S31b-S32b.
[0142] Step S31b: Under the conditions of temperature of 1900~2100℃ and pressure of 0.001~0.03pa, the carbon surface of the silicon carbide transition layer is heterobonded to the surface of the initial diamond layer to obtain the second heterobonded structure.
[0143] The surface roughness of the initial diamond layer is less than a fourth preset roughness, which ranges from 1 to 5 nm. The surface roughness of the initial diamond layer can be 0.5 nm, 1 nm, 2 nm, 3 nm, or 4 nm.
[0144] For example, the temperature can be 1900℃, 1950℃, 2000℃, 2050℃ or 2100℃; the air pressure can be 0.001pa, 0.005pa, 0.01pa, 0.015pa, 0.02pa, 0.025pa or 0.03pa.
[0145] Through in-depth research, the inventors discovered that during heterogeneous bonding, if the temperature is below 1900℃, the bonding is weak and defects such as voids and microcracks are easily generated at the interface; if the temperature is above 2100℃, power consumption is excessive and it has little effect on improving the bonding strength. If the gas pressure is above 0.03Pa, the vacuum level is not high, and impurities such as air are easily introduced, affecting the bonding effect; if the gas pressure is below 0.001Pa, the requirements for system equipment are very high, resulting in high costs. Therefore, it is necessary to control the temperature and gas pressure of heterogeneous bonding within the above-mentioned ranges.
[0146] Under the above conditions, heterogeneous bonding (both bonding surfaces are carbon surfaces) is carried out. The lattice mismatch between the silicon carbide transition layer and the initial diamond layer is small, and the solid-solid interface energy is very low. It is easy to achieve carbon surface bonding without intermediate layers. This not only promotes the formation of chemical bonds between the two and reduces the density of interface defects, but also makes the surfaces of the two in close contact, reduces micropores and gaps, and improves the compactness and mechanical strength of the second heterogeneous bonding structure.
[0147] Furthermore, it can reduce the residual stress at the interface caused by the difference in thermal expansion between the silicon carbide transition layer and the initial diamond layer, preventing cracking of the second heterobonded structure. In addition, heterobonding under these conditions results in low interfacial thermal resistance, and the high thermal conductivity of diamond can quickly conduct away the heat accumulated in the silicon carbide transition layer, thereby establishing a larger temperature gradient in the vertical and horizontal directions within the silicon carbide composite seed crystal.
[0148] Furthermore, the initial diamond layer can be first precision ground using diamond polishing slurry, and then chemically and mechanically polished to achieve a surface roughness of less than 1–5 nm. Post-processing of the initial diamond layer includes steps S27b–S29b.
[0149] Step S27b: Acid wash the polished initial diamond layer.
[0150] For example, the initial diamond layer can be soaked in aqua regia (a mixture of nitric acid and hydrochloric acid) for 30 minutes to remove contaminant particles from the surface of the initial diamond layer.
[0151] Step S28b: Perform ultrasonic cleaning on the initial diamond layer after acid washing.
[0152] For example, ultrasonic cleaning of the initial diamond layer with acetone solution for 10 minutes is used to penetrate the microporous structure of the initial diamond layer surface, achieving thorough cleaning without dead angles. This not only further removes contaminants and polishing reagent residues from the surface of the initial diamond layer, but also creates micro-scratches on the surface of the initial diamond layer, optimizing its surface morphology. This, in turn, increases the nucleation density and bonding strength of the subsequent silicon carbide transition layer, allowing the nucleation density to reach as high as 10. 9 / cm 2 .
[0153] Step S29b: Dry the initial diamond layer after ultrasonic cleaning.
[0154] For example, the initial diamond layer is baked in an oven at 200°C for 15 minutes to dry the initial diamond layer.
[0155] Through the above steps, efficient decontamination of the initial diamond layer is achieved, ensuring the integrity and high cleanliness of its surface. This reduces defects caused by contaminants during subsequent bonding processes, ensuring that the number of particles (0.3μm scale) on the surface of the initial diamond layer is less than 500-1000, thus ensuring the uniformity and adhesion of the bonding between the carbon surface of the silicon carbide transition layer and the surface of the initial diamond layer.
[0156] As a preferred embodiment of this application, before heterobonding the carbon surface of the silicon carbide transition layer with the initial diamond layer, the preparation method further includes step S30b: forming a plurality of second microchannels in the form of protrusions or grooves on the surface of the initial diamond layer.
[0157] In a preferred embodiment of step S30b, step S30b includes: forming a plurality of second microchannels in the form of protrusions or grooves on the surface of the initial diamond layer by laser etching under the conditions of a pulse width of 500ps to 1ns, a laser power of 10 to 15W, and a laser repetition frequency of 20 to 100kHz.
[0158] For example, the laser wavelength is 1064nm, 532nm, or 355nm; the pulse width is 500ps, 600ps, 700ps, 800ps, 900ps, or 1ns; the laser power is 10W, 11W, 12W, 13W, 14W, or 15W; and the laser repetition frequency is 20kHz, 30kHz, 40kHz, 50kHz, 60kHz, 70kHz, 80kHz, 90kHz, or 100kHz.
[0159] As another preferred embodiment of step S30b, step S30b includes: forming a plurality of second microchannels in the form of protrusions or grooves on the surface of the initial diamond layer by plasma etching under the conditions of etching temperature exceeding 1800°C and etching gas being CF4, O2 or Ar.
[0160] For preferred options, please refer to the appendix. Figure 3 As shown, all the second microchannels are connected end to end and distributed in a vortex pattern (mosquito coil pattern). The etching width of the second microchannel is 5-10 μm, for example, it can be 5 μm, 6 μm, 7 μm, 8 μm, 9 μm or 10 μm; the etching depth of the second microchannel is 30-50 μm, for example, it can be 30 μm, 35 μm, 40 μm, 45 μm or 50 μm; the lateral spacing of the second microchannel is 5-10 mm, for example, it can be 5 mm, 6 mm, 7 mm, 8 mm, 9 mm or 10 mm.
[0161] For example, the etching temperature can be 1800°C, 1850°C, 1900°C, 2000°C or 2100°C.
[0162] By setting a second microchannel, the contact surface area between the silicon carbide transition layer and the diamond layer can be increased, thereby enhancing the heat transfer capacity of the silicon carbide transition layer and the diamond layer during the growth process, which helps to establish a larger temperature gradient in the vertical and horizontal directions for the silicon carbide composite seed crystal.
[0163] It should be noted that the raised first microchannel corresponds to the grooved second microchannel so that the raised first microchannel can be embedded in the grooved second microchannel; the raised second microchannel corresponds to the grooved first microchannel so that the raised second microchannel can be embedded in the grooved first microchannel.
[0164] During the bonding process, the corresponding interlocking of the first and second microchannels can further increase the contact surface area between the initial diamond layer and the silicon carbide transition layer, thereby enhancing the heat transfer capacity of the diamond layer and the silicon carbide transition layer during growth, which helps to establish a larger temperature gradient in the vertical and horizontal directions for the silicon carbide composite seed crystal.
[0165] Step S32b: After heterobonding is completed, the second heterobonded structure is annealed for 20 to 40 hours at an annealing temperature of 1800 to 1900°C and an annealing atmosphere of argon or nitrogen, so that the initial diamond layer is transformed into a diamond layer with a thickness of 300 to 500 μm.
[0166] The purpose of annealing is to eliminate lattice deformation caused by the diffusion of carbon atoms in silicon carbide and diamond materials, and to reduce or eliminate thermal stress in the bonding interface.
[0167] For example, the annealing temperature can be 1800℃, 1820℃, 1850℃, 1880℃ or 1900℃; the annealing time can be 20h, 22h, 25h, 28h, 30h, 32h, 35h, 38h or 40h.
[0168] The inventors discovered that annealing below 1800℃, exceeding the aforementioned temperature range, results in poor removal of thermal stress and fails to effectively eliminate the thermal stress generated by bonding. Annealing at 1900℃ effectively removes internal thermal stress; further increases in temperature lead to high electricity costs and are not worthwhile. Similarly, the annealing time also needs to be controlled within the aforementioned range. Therefore, it is necessary to control the annealing temperature and time within the aforementioned range.
[0169] By annealing the second heterobonded structure under the above conditions, not only can the internal thermal stress generated during the bonding process be reduced, but the physical diffusion of carbon atoms can also be promoted at high temperature, thereby reducing the interfacial thermal resistance.
[0170] In summary, this application enables the epitaxial growth of a silicon carbide transition layer on the silicon surface of a silicon carbide seed crystal via chemical vapor deposition, and the growth of a diamond layer on the carbon surface of the silicon carbide transition layer via chemical vapor deposition, thereby achieving the preparation of a silicon carbide composite seed crystal.
[0171] This application can also grow a silicon carbide transition layer on the silicon surface of the silicon carbide seed crystal through heterobonding, and grow a diamond layer on the carbon surface of the silicon carbide transition layer through chemical vapor deposition, thereby realizing the preparation of silicon carbide composite seed crystals.
[0172] This application can also bond the silicon surface of the silicon carbide seed crystal to the silicon surface of the silicon carbide transition layer through heterobonding, and bond the carbon surface of the silicon carbide transition layer to the surface of the diamond layer through heterobonding, thereby realizing the preparation of silicon carbide composite seed crystals.
[0173] This application can also grow a silicon carbide transition layer on the silicon surface of the silicon carbide seed crystal by vapor phase chemical deposition, and then bond the silicon surface of the silicon carbide transition layer to the diamond layer surface by heterogeneous bonding to achieve the preparation of silicon carbide composite seed crystal.
[0174] This application can also form a silicon carbide transition layer on the silicon surface of the silicon carbide seed crystal, and etch a first microchannel on the carbon surface of the silicon carbide transition layer, so that the carbon surface of the silicon carbide transition layer with the first microchannel is bonded to the surface of the diamond layer, thereby realizing the preparation of silicon carbide composite seed crystal.
[0175] This application can also form a silicon carbide transition layer on the silicon surface of the silicon carbide seed crystal, and etch a second microchannel on the surface of the diamond layer, so that the surface of the diamond layer with the second microchannel is combined with the carbon surface of the silicon carbide transition layer, thereby realizing the preparation of silicon carbide composite seed crystal.
[0176] This application can also form a silicon carbide transition layer on the silicon surface of the silicon carbide seed crystal, etch a first microchannel on the carbon surface of the silicon carbide transition layer, and etch a second microchannel on the surface of the diamond layer, so that the carbon surface of the silicon carbide transition layer with the first microchannel is combined with the surface of the diamond layer with the second microchannel, thereby realizing the preparation of silicon carbide composite seed crystal.
[0177] Furthermore, the bonding in this application is direct bonding under normal pressure without an intermediate bonding layer; the bonding in this application is permanent bonding. After the silicon carbide crystal growth is completed on the silicon carbide composite seed crystal, the diamond layer can be cut out using laser cutting technology, and then the diamond layer can be ground and polished so that the diamond material can be used repeatedly to prepare silicon carbide composite seed crystals.
[0178] This application utilizes the extremely high thermal conductivity of diamond (2000-2200 W / (m·K)) to rapidly conduct the heat accumulated in the silicon carbide seed crystal along the vertical direction, thereby reducing the temperature of the silicon carbide seed crystal. During thick crystal growth, the required vertical temperature gradient is determined by the temperature difference between the diamond layer at the bottom of the growth chamber and the silicon carbide seed crystal at the top. The temperature of the silicon carbide seed crystal is lower than that of the diamond layer. The greater the temperature difference, the greater the vertical temperature gradient within a certain spacing range. This vertical temperature gradient is the crystallization driving force required for the growth of thick silicon carbide crystals. The greater the vertical temperature gradient, the greater the vertical crystallization driving force, and the faster the crystal grows vertically. Thus, thick silicon carbide crystals can be grown within the same growth cycle.
[0179] The horizontal temperature gradient required during the growth of large-diameter crystals is determined by the temperature difference between the silicon carbide seed crystal located at the top of the growth chamber and the temperature of the inner wall of the growth chamber. The inner wall temperature is higher than the silicon carbide seed crystal temperature. The greater the temperature difference between the two, the greater the horizontal temperature gradient within a certain spacing range. This horizontal temperature gradient is the crystallization driving force required for the growth of large-diameter silicon carbide crystals. The greater the horizontal temperature gradient, the greater the horizontal crystallization driving force, and the faster the crystal grows in the vertical direction. In the same growth cycle, large-diameter silicon carbide crystals can be grown.
[0180] Therefore, the silicon carbide composite seed crystal provided in this application can establish a large temperature gradient in both the vertical and horizontal directions. This can accelerate the growth rate of silicon carbide crystals in the vertical direction, which is beneficial for the rapid growth of silicon carbide crystals with a thickness of more than 50 mm. It can also increase the growth rate of silicon carbide crystals in the horizontal direction, which is beneficial for the rapid expansion of the diameter of silicon carbide crystals during growth. This makes it easier to achieve the growth of large-diameter silicon carbide crystals and greatly reduces the growth cost of silicon carbide materials. This method can save more than 60% of high-quality silicon carbide materials. In summary, the silicon carbide composite seed crystal prepared by the above method can achieve the growth of large-diameter, high-thickness, and low-cost silicon carbide crystals while ensuring the growth quality of silicon carbide crystals.
[0181] In a second aspect of this embodiment, a silicon carbide composite seed crystal is provided, which is prepared by the above-described method for preparing silicon carbide composite seed crystals.
[0182] like Figure 2 As shown, the silicon carbide composite seed crystal 10 includes a silicon carbide seed crystal 11, a silicon carbide transition layer 12, and a diamond layer 13. The silicon carbide transition layer 12 is disposed on the silicon carbide seed crystal 11; the diamond layer 13 is disposed on the side of the silicon carbide transition layer 12 away from the silicon carbide seed crystal 11.
[0183] In a third aspect of this embodiment, a silicon carbide crystal is provided, the silicon carbide crystal comprising the aforementioned silicon carbide composite seed crystal.
[0184] The technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.
[0185] It should be noted that, unless otherwise specified in the following examples, the conditions should be performed under standard conditions or conditions recommended by the manufacturer. Reagents or instruments whose manufacturers are not specified are all commercially available products.
[0186] Example 1
[0187] This embodiment provides a method for preparing silicon carbide composite seed crystals, including the following steps:
[0188] S11: Provides silicon carbide seed crystals with a thickness of 140μm and a surface roughness of 1nm.
[0189] S12: Under the conditions of temperature of 850℃, gas pressure of 20Kpa, flow rates of SiH4 and CH4 of 2sccm and flow rate of H2 of 200sccm, an initial silicon carbide transition layer with a thickness of 50μm was obtained by chemical vapor deposition on the surface of silicon carbide seed crystal for 10h.
[0190] S13: Grind and polish the initial silicon carbide transition layer to transform it into a silicon carbide transition layer with a thickness of 10 μm and a surface roughness of 1 nm, thus obtaining a silicon carbide composite structure.
[0191] S14: Under the conditions of temperature of 850℃, gas pressure of 20Kpa, flow rates of CH4 and O2 of 2sccm and flow rate of H2 of 200sccm, an initial diamond layer with a thickness of 500μm was obtained by MPCVD growth on the silicon surface of the silicon carbide transition layer for 60h.
[0192] S15: Grind and polish the initial diamond layer to obtain a diamond layer with a thickness of 300μm and a surface roughness of 1nm, thus obtaining a silicon carbide composite seed crystal.
[0193] Example 2
[0194] This embodiment provides a method for preparing silicon carbide composite seed crystals, including the following steps:
[0195] S11: Provides silicon carbide seed crystals with a thickness of 200μm and a surface roughness of 4nm.
[0196] S12: Under the conditions of 900℃, 30Kpa, 20sccm flow rates of SiH4 and CH4, and 500sccm flow rate of H2, an initial silicon carbide transition layer with a thickness of 200μm was obtained by chemical vapor deposition on the surface of a silicon carbide seed crystal for 20h.
[0197] S13: Grind and polish the initial silicon carbide transition layer to transform it into a silicon carbide transition layer with a thickness of 50 μm and a surface roughness of 4 nm, thus obtaining a silicon carbide composite structure.
[0198] S14: Under the conditions of 900℃, 30Kpa, CH4 and O2 flow rates of 20sccm and H2 flow rate of 500sccm, an initial diamond layer with a thickness of 900μm was obtained by MPCVD growth on the silicon surface of the silicon carbide transition layer for 90h.
[0199] S15: Grind and polish the initial diamond layer to obtain a diamond layer with a thickness of 480μm and a surface roughness of 4nm, thus obtaining a silicon carbide composite seed crystal.
[0200] Example 3
[0201] This embodiment provides a method for preparing silicon carbide composite seed crystals, including the following steps:
[0202] S11: Provides silicon carbide seed crystals with a thickness of 150μm and a surface roughness of 3nm.
[0203] S12: An initial silicon carbide transition layer with a thickness of 125 μm was obtained by chemical vapor deposition on the surface of a silicon carbide seed crystal under the conditions of a temperature of 875℃, a gas pressure of 25 kPa, a flow rate of 12 sccm for both SiH4 and CH4, and a flow rate of 350 sccm for H2.
[0204] S13: Grind and polish the initial silicon carbide transition layer to transform it into a silicon carbide transition layer with a thickness of 30 μm and a surface roughness of 3 nm, thus obtaining a silicon carbide composite structure.
[0205] S14: Under the conditions of a temperature of 875℃, a gas pressure of 25Kpa, a flow rate of CH4 and O2 of 12sccm and a flow rate of H2 of 350sccm, an initial diamond layer with a thickness of 700μm was obtained by MPCVD growth on the silicon surface of the silicon carbide transition layer for 75h.
[0206] S15: Grind and polish the initial diamond layer to obtain a diamond layer with a thickness of 350μm and a surface roughness of 3nm, thus obtaining a silicon carbide composite seed crystal.
[0207] Example 4
[0208] This embodiment provides a method for preparing silicon carbide composite seed crystals, including the following steps:
[0209] S11: Provides silicon carbide seed crystals with a thickness of 140μm and a surface roughness of 1nm.
[0210] S12: Under the conditions of temperature of 1900℃ and pressure of 0.001pa, the silicon surface of the silicon carbide seed crystal is heterobonded with the silicon surface of the initial silicon carbide transition layer with a surface roughness of 1nm and a thickness of 10μm to obtain the first heterobonded structure.
[0211] S13: After heterobonding is completed, the first heterobonded structure is annealed for 20 hours at an annealing temperature of 1800℃ and an annealing atmosphere of argon or nitrogen, so that the initial silicon carbide transition layer is transformed into a silicon carbide transition layer with a thickness of 10μm, thus obtaining a silicon carbide composite structure.
[0212] S14: Under the conditions of temperature of 850℃, gas pressure of 20Kpa, flow rates of CH4 and O2 of 2sccm and flow rate of H2 of 200sccm, an initial diamond layer with a thickness of 500μm was obtained by MPCVD growth on the silicon surface of the silicon carbide transition layer for 60h.
[0213] S15: Grind and polish the initial diamond layer to obtain a diamond layer with a thickness of 300μm and a surface roughness of 1nm, thus obtaining a silicon carbide composite seed crystal.
[0214] Example 5
[0215] This embodiment provides a method for preparing silicon carbide composite seed crystals, including the following steps:
[0216] S11: Provides silicon carbide seed crystals with a thickness of 200μm and a surface roughness of 4nm.
[0217] S12: Under the conditions of temperature of 2100℃ and pressure of 0.03pa, the silicon surface of the silicon carbide seed crystal is heterobonded with the silicon surface of the initial silicon carbide transition layer with a surface roughness of 4nm and a thickness of 50μm to obtain the first heterobonded structure.
[0218] S13: After heterobonding is completed, the first heterobonded structure is annealed for 40 hours at an annealing temperature of 1900℃ and an annealing atmosphere of argon or nitrogen, so that the initial silicon carbide transition layer is transformed into a silicon carbide transition layer with a thickness of 50μm, thus obtaining a silicon carbide composite structure.
[0219] S14: Under the conditions of 900℃, 30Kpa, CH4 and O2 flow rates of 20sccm and H2 flow rate of 500sccm, an initial diamond layer with a thickness of 900μm was obtained by MPCVD growth on the silicon surface of the silicon carbide transition layer for 90h.
[0220] S15: Grind and polish the initial diamond layer to obtain a diamond layer with a thickness of 480μm and a surface roughness of 4nm, thus obtaining a silicon carbide composite seed crystal.
[0221] Example 6
[0222] This embodiment provides a method for preparing silicon carbide composite seed crystals, including the following steps:
[0223] S11: Provides silicon carbide seed crystals with a thickness of 150μm and a surface roughness of 3nm.
[0224] S12: Under the conditions of 2000℃ and 0.02pa, the silicon surface of the silicon carbide seed crystal is heterobonded with the silicon surface of the initial silicon carbide transition layer with a surface roughness of 3nm and a thickness of 30μm to obtain the first heterobonded structure.
[0225] S13: After heterobonding is completed, the first heterobonded structure is annealed for 30 hours at an annealing temperature of 1850℃ and an annealing atmosphere of argon or nitrogen, so that the initial silicon carbide transition layer is transformed into a silicon carbide transition layer with a thickness of 30μm, thus obtaining a silicon carbide composite structure.
[0226] S14: Under the conditions of a temperature of 875℃, a gas pressure of 25Kpa, a flow rate of CH4 and O2 of 12sccm and a flow rate of H2 of 350sccm, an initial diamond layer with a thickness of 700μm was obtained by MPCVD growth on the silicon surface of the silicon carbide transition layer for 75h.
[0227] S15: Grind and polish the initial diamond layer to obtain a diamond layer with a thickness of 350μm and a surface roughness of 3nm, thus obtaining a silicon carbide composite seed crystal.
[0228] Example 7
[0229] This embodiment provides a method for preparing silicon carbide composite seed crystals, including the following steps:
[0230] S11: Provides silicon carbide seed crystals with a thickness of 140μm and a surface roughness of 1nm.
[0231] S12: Under the conditions of temperature of 1900℃ and pressure of 0.001pa, the silicon surface of the silicon carbide seed crystal is heterobonded with the silicon surface of the initial silicon carbide transition layer with a surface roughness of 1nm and a thickness of 10μm to obtain the first heterobonded structure.
[0232] S13: After heterobonding is completed, the first heterobonded structure is annealed for 20 hours at an annealing temperature of 1800℃ and an annealing atmosphere of argon or nitrogen, so that the initial silicon carbide transition layer is transformed into a silicon carbide transition layer with a thickness of 10μm, thus obtaining a silicon carbide composite structure.
[0233] S14: Under the conditions of temperature of 1900℃ and pressure of 0.001pa, the carbon surface of the silicon carbide transition layer is heterobonded with an initial diamond layer with a surface roughness of 1nm and a thickness of 300μm to obtain a second heterobonded structure.
[0234] S15: After heterobonding is completed, the second heterobonded structure is annealed for 20 hours at an annealing temperature of 1800℃ and an annealing atmosphere of argon or nitrogen, so that the initial diamond layer is transformed into a diamond layer with a thickness of 300μm and a surface roughness of 1nm, thus obtaining a silicon carbide composite seed crystal.
[0235] Example 8
[0236] This embodiment provides a method for preparing silicon carbide composite seed crystals, including the following steps:
[0237] S11: Provides silicon carbide seed crystals with a thickness of 200μm and a surface roughness of 4nm.
[0238] S12: Under the conditions of temperature of 2100℃ and pressure of 0.03pa, the silicon surface of the silicon carbide seed crystal is heterobonded with the silicon surface of the initial silicon carbide transition layer with a surface roughness of 4nm and a thickness of 50μm to obtain the first heterobonded structure.
[0239] S13: After heterobonding is completed, the first heterobonded structure is annealed for 40 hours at an annealing temperature of 1900℃ and an annealing atmosphere of argon or nitrogen, so that the initial silicon carbide transition layer is transformed into a silicon carbide transition layer with a thickness of 50μm, thus obtaining a silicon carbide composite structure.
[0240] S14: Under the conditions of temperature of 2100℃ and pressure of 0.03pa, the carbon surface of the silicon carbide transition layer is heterobonded with an initial diamond layer with a surface roughness of 4nm and a thickness of 480μm to obtain a second heterobonded structure.
[0241] S15: After heterobonding is completed, the second heterobonded structure is annealed for 40 hours at an annealing temperature of 1900℃ and an annealing atmosphere of argon or nitrogen, so that the initial diamond layer is transformed into a diamond layer with a thickness of 480μm and a surface roughness of 5nm, thus obtaining a silicon carbide composite seed crystal.
[0242] Example 9
[0243] This embodiment provides a method for preparing silicon carbide composite seed crystals, including the following steps:
[0244] S11: Provides silicon carbide seed crystals with a thickness of 150μm and a surface roughness of 3nm.
[0245] S12: Under the conditions of 2000℃ and 0.02pa, the silicon surface of the silicon carbide seed crystal is heterobonded with the silicon surface of the initial silicon carbide transition layer with a surface roughness of 3nm and a thickness of 30μm to obtain the first heterobonded structure.
[0246] S13: After heterobonding is completed, the first heterobonded structure is annealed for 30 hours at an annealing temperature of 1850℃ and an annealing atmosphere of argon or nitrogen, so that the initial silicon carbide transition layer is transformed into a silicon carbide transition layer with a thickness of 30μm, thus obtaining a silicon carbide composite structure.
[0247] S14: Under the conditions of 2000℃ and 0.02pa, the carbon surface of the silicon carbide transition layer is heterobonded with an initial diamond layer with a surface roughness of 3nm and a thickness of 350μm to obtain a second heterobonded structure.
[0248] S15: After heterobonding is completed, the second heterobonded structure is annealed for 30 hours at an annealing temperature of 1850℃ and an annealing atmosphere of argon or nitrogen, so that the initial diamond layer is transformed into a diamond layer with a thickness of 350μm and a surface roughness of 3nm, thus obtaining a silicon carbide composite seed crystal.
[0249] Example 10
[0250] This embodiment provides a method for preparing silicon carbide composite seed crystals, including the following steps:
[0251] S11: Provides silicon carbide seed crystals with a thickness of 140μm and a surface roughness of 1nm.
[0252] S12: Under the conditions of temperature of 850℃, gas pressure of 20Kpa, flow rates of SiH4 and CH4 of 2sccm and flow rate of H2 of 200sccm, an initial silicon carbide transition layer with a thickness of 50μm was obtained by chemical vapor deposition on the surface of silicon carbide seed crystal for 10h.
[0253] S13: Grind and polish the initial silicon carbide transition layer to transform it into a silicon carbide transition layer with a thickness of 10 μm and a surface roughness of 1 nm, thus obtaining a silicon carbide composite structure.
[0254] S14: Under the conditions of temperature of 1900℃ and pressure of 0.001pa, the carbon surface of the silicon carbide transition layer is heterobonded with an initial diamond layer with a surface roughness of 1nm and a thickness of 300μm to obtain a second heterobonded structure.
[0255] S15: After heterobonding is completed, the second heterobonded structure is annealed for 20 hours at an annealing temperature of 1800℃ and an annealing atmosphere of argon or nitrogen, so that the initial diamond layer is transformed into a diamond layer with a thickness of 300μm and a surface roughness of 1nm, thus obtaining a silicon carbide composite seed crystal.
[0256] Example 11
[0257] This embodiment provides a method for preparing silicon carbide composite seed crystals, including the following steps:
[0258] S11: Provides silicon carbide seed crystals with a thickness of 200μm and a surface roughness of 4nm.
[0259] S12: Under the conditions of 900℃, 30Kpa, 20sccm flow rates of SiH4 and CH4, and 500sccm flow rate of H2, an initial silicon carbide transition layer with a thickness of 200μm was obtained by chemical vapor deposition on the surface of a silicon carbide seed crystal for 20h.
[0260] S13: Grind and polish the initial silicon carbide transition layer to transform it into a silicon carbide transition layer with a thickness of 50 μm and a surface roughness of 4 nm, thus obtaining a silicon carbide composite structure.
[0261] S14: Under the conditions of temperature of 2100℃ and pressure of 0.03pa, the carbon surface of the silicon carbide transition layer is heterobonded with an initial diamond layer with a surface roughness of 4nm and a thickness of 480μm to obtain a second heterobonded structure.
[0262] S15: After heterobonding is completed, the second heterobonded structure is annealed for 40 hours at an annealing temperature of 1900℃ and an annealing atmosphere of argon or nitrogen, so that the initial diamond layer is transformed into a diamond layer with a thickness of 480μm and a surface roughness of 4nm, thus obtaining a silicon carbide composite seed crystal.
[0263] Example 12
[0264] This embodiment provides a method for preparing silicon carbide composite seed crystals, including the following steps:
[0265] S11: Provides silicon carbide seed crystals with a thickness of 150μm and a surface roughness of 3nm.
[0266] S12: An initial silicon carbide transition layer with a thickness of 125 μm was obtained by chemical vapor deposition on the surface of a silicon carbide seed crystal under the conditions of a temperature of 875℃, a gas pressure of 25 kPa, a flow rate of 12 sccm for both SiH4 and CH4, and a flow rate of 350 sccm for H2.
[0267] S13: Grind and polish the initial silicon carbide transition layer to transform it into a silicon carbide transition layer with a thickness of 30 μm and a surface roughness of 3 nm, thus obtaining a silicon carbide composite structure.
[0268] S14: Under the conditions of 2000℃ and 0.02pa, the carbon surface of the silicon carbide transition layer is heterobonded with an initial diamond layer with a surface roughness of 3nm and a thickness of 350μm to obtain a second heterobonded structure.
[0269] S15: After heterobonding is completed, the second heterobonded structure is annealed for 30 hours at an annealing temperature of 1850℃ and an annealing atmosphere of argon or nitrogen, so that the initial diamond layer is transformed into a diamond layer with a thickness of 350μm and a surface roughness of 3nm, thus obtaining a silicon carbide composite seed crystal.
[0270] Example 13
[0271] Similar to the preparation method in Example 1, the difference is as follows: S14: Under the conditions of temperature of 2200℃, gas pressure of 20Kpa, CH4 flow rate of 2sccm and H2 flow rate of 200sccm, HFCVD is used to grow on the carbon surface of the silicon carbide transition layer for 60h to prepare an initial diamond layer with a thickness of 500μm; the rest are the same and will not be described in detail here.
[0272] Example 14
[0273] Similar to the preparation method in Example 2, the difference is as follows: S14: Under the conditions of temperature of 2300℃, gas pressure of 30Kpa, CH4 flow rate of 20sccm and H2 flow rate of 500sccm, HFCVD is used to grow on the carbon surface of the silicon carbide transition layer for 90h to prepare an initial diamond layer with a thickness of 900μm; the rest are the same and will not be described in detail here.
[0274] Example 15
[0275] Similar to the preparation method in Example 3, the difference is as follows: S14: Under the conditions of temperature of 2250℃, gas pressure of 25Kpa, CH4 flow rate of 12sccm and H2 flow rate of 350sccm, HFCVD is used to grow on the carbon surface of the silicon carbide transition layer for 75h to prepare an initial diamond layer with a thickness of 700μm; the rest are the same and will not be described in detail here.
[0276] Example 16
[0277] Similar to the preparation method in Example 4, the difference is as follows: S14: Under the conditions of temperature of 850°C, gas pressure of 20 kPa, CH4 flow rate of 2 sccm and H2 flow rate of 200 sccm, DCPCVD is used to grow on the carbon surface of the silicon carbide transition layer for 5 h to prepare an initial diamond layer with a thickness of 500 μm; the rest are the same and will not be described in detail here.
[0278] Example 17
[0279] Similar to the preparation method in Example 5, the difference is that: under the conditions of a temperature of 900°C, a gas pressure of 30 kPa, a CH4 flow rate of 20 sccm and an H2 flow rate of 500 sccm, DCPCVD was used to grow on the carbon surface of the silicon carbide transition layer for 10 h to prepare an initial diamond layer with a thickness of 900 μm.
[0280] Example 18
[0281] Similar to the preparation method in Example 6, the difference is that: under the conditions of a temperature of 875°C, a gas pressure of 25 kPa, a CH4 flow rate of 12 sccm and an H2 flow rate of 350 sccm, DCPCVD was used to grow on the carbon surface of the silicon carbide transition layer for 7 h to prepare an initial diamond layer with a thickness of 700 μm.
[0282] Example 19
[0283] Similar to the preparation method in Example 3, the difference is that a groove-shaped first microchannel is formed by etching on the carbon surface of the silicon carbide transition layer; the rest is the same and will not be described again here.
[0284] The width of the first microchannel is 5μm, the depth of the first microchannel is 30μm, and the lateral spacing of the first microchannel is 5mm.
[0285] Example 20
[0286] The preparation method is similar to that in Example 12, except that a raised second microchannel is formed by etching on the surface of the initial diamond layer; the rest is the same and will not be described again here.
[0287] The width of the second microchannel is 5μm, the depth of the first microchannel is 30μm, and the lateral spacing of the first microchannel is 5mm.
[0288] Example 21
[0289] Similar to the preparation method in Example 9, the difference is that a groove-shaped first microchannel is etched on the carbon surface of the silicon carbide transition layer, and a raised second microchannel is etched on the surface of the initial diamond layer; the rest are the same and will not be described again here.
[0290] The width of the first microchannel is 5μm, the depth of the first microchannel is 30μm, and the lateral spacing of the first microchannel is 5mm; the width of the second microchannel is 5μm, the depth of the first microchannel is 30μm, and the lateral spacing of the first microchannel is 5mm.
[0291] Silicon carbide crystals were grown using the silicon carbide composite seed crystals prepared in Examples 1-21, under the following growth conditions: growth temperature of 2200-2300℃ and pressure of 3×10⁻⁶. -3 pa-5×10 -3 The growth period is 160-200 hours.
[0292] The grown silicon carbide crystals have a diameter of 200 mm and a thickness of 40 mm, with an average growth rate of 200-250 μm / hour. The grown silicon carbide crystals have a smooth surface, good light transmittance, and no polycrystalline phenomenon; these silicon carbide crystals are single 4H crystals.
[0293] Under the above growth conditions (i.e., growth temperature of 2200-2300℃, pressure of 3×10⁻⁶), -3 pa-5×10 -3 Under conditions of 160-200 hours (Pa and growth time), silicon carbide crystals were grown using pure silicon carbide seed crystals. The grown silicon carbide crystals had a diameter of 150 mm and a thickness of 30 mm, with an average growth rate of 150-200 μm / hour. The surface of the silicon carbide crystals was uneven, with poor light transmittance and polycrystalline structure.
[0294] Therefore, it can be seen that compared with existing pure silicon carbide seed crystals, the silicon carbide composite seed crystal provided in this application results in a faster average growth rate, producing thicker and larger diameter silicon carbide crystals. Furthermore, the grown silicon carbide crystals have a smooth surface, good light transmittance, no polycrystalline structure, and are of superior quality. Moreover, the thickness of the silicon carbide seed crystal in the silicon carbide composite seed crystal provided in this application accounts for less than 1 / 3 of the total thickness. Therefore, compared with existing pure silicon carbide seed crystals, the silicon carbide composite seed crystal provided in this application can save at least 2 / 3 of the silicon carbide seed crystal usage.
[0295] Although embodiments of this application have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting this application. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of the invention without departing from the principles and spirit of this application, and all such changes should fall within the protection scope of the claims of this application.
Claims
1. A method for preparing silicon carbide composite seed crystals, characterized in that, Includes the following steps: Provide silicon carbide seed crystals; A silicon carbide transition layer is formed on the silicon surface of the silicon carbide seed crystal, and the carbon surface of the silicon carbide transition layer is moved away from the silicon surface of the silicon carbide seed crystal to obtain a silicon carbide composite structure. A diamond layer is formed on the carbon surface of the silicon carbide transition layer to obtain a silicon carbide composite seed crystal; The thermal conductivity of the silicon carbide transition layer is less than that of the diamond layer, and the thermal conductivity of the silicon carbide transition layer is greater than that of the silicon carbide seed crystal; the crystal form of the silicon carbide transition layer is different from that of the silicon carbide seed crystal.
2. The preparation method according to claim 1, characterized in that, During the formation of the silicon carbide transition layer on the silicon surface of the silicon carbide seed crystal, the silicon surface of the silicon carbide seed crystal and the silicon surface of the silicon carbide transition layer are bonded together by silicon atom diffusion; the formation of the silicon carbide transition layer on the silicon surface of the silicon carbide seed crystal includes: Under conditions of temperature of 850–900℃, gas pressure of 20–30 kPa, flow rates of SiH4 and CH4 of 2–20 sccm, and flow rate of H2 of 200–500 sccm, an initial silicon carbide transition layer of 50–200 μm thickness was prepared by chemical vapor deposition for 10–20 h on the silicon surface of the silicon carbide seed crystal with a thickness of 100–200 μm. The carbon surface of the initial silicon carbide transition layer is ground and polished to obtain a silicon carbide transition layer with a thickness of 10-50 μm and a surface roughness less than the first preset roughness. The value range of the first preset roughness is 1 to 5 nm.
3. The preparation method according to claim 1, characterized in that, During the formation of the silicon carbide transition layer on the silicon surface of the silicon carbide seed crystal, the silicon surface of the silicon carbide seed crystal and the silicon surface of the silicon carbide transition layer are bonded together by silicon atom diffusion; the formation of the silicon carbide transition layer on the silicon surface of the silicon carbide seed crystal includes: Under conditions of temperature of 1900–2100℃ and pressure of 0.001–0.03 Pa, the silicon surface of a silicon carbide seed crystal with a thickness of 100–200 μm is heterobonded to the silicon surface of the initial silicon carbide transition layer to obtain the first heterobonded structure. Wherein, the surface roughness of the silicon surface of the initial silicon carbide transition layer is less than the second preset roughness, and the value range of the second preset roughness is 1 to 5 nm; After heterobonding is completed, the first heterobonded structure is annealed for 20 to 40 hours at an annealing temperature of 1800 to 1900°C and an annealing atmosphere of argon or nitrogen, so that the initial silicon carbide transition layer is transformed into the silicon carbide transition layer. The thickness of the silicon carbide transition layer is 10–50 μm.
4. The preparation method according to any one of claims 1-3, characterized in that, During the formation of a diamond layer on the carbon facet of the silicon carbide transition layer, the carbon facet of the silicon carbide transition layer and the surface of the diamond layer are bonded together through carbon atom diffusion; the formation of a diamond layer on the carbon facet of the silicon carbide transition layer includes: An initial diamond layer with a thickness of 500-900 μm was grown on the carbon surface of the silicon carbide transition layer using chemical vapor deposition. The initial diamond layer is ground and polished to obtain a diamond layer with a thickness of 300-500 μm and a surface roughness less than a third preset roughness; The value range of the third preset roughness is 1 to 5 nm.
5. The preparation method according to claim 4, characterized in that, The initial diamond layer with a thickness of 500-900 μm grown on the carbon surface of the silicon carbide transition layer includes: Under conditions of temperature of 850–900℃, pressure of 20–30 kPa, flow rate of CH4 of 2–20 sccm, flow rate of H2 of 200–500 sccm, and flow rate of O2 of 2–20 sccm, MPCVD is used to grow the carbon surface of the silicon carbide transition layer for 60–90 h to prepare the initial diamond layer with a thickness of 500–900 μm. Alternatively, under conditions of a temperature of 2200–2300 °C, a gas pressure of 20–30 kPa, a CH4 flow rate of 2–20 sccm, and an H2 flow rate of 200–500 sccm, HFCVD is used to grow the carbon surface of the silicon carbide transition layer for 60–90 h to prepare the initial diamond layer with a thickness of 500–900 μm. Alternatively, under conditions of 850–900 °C, 20–30 kPa, CH4 flow rate of 2–20 sccm, and H2 flow rate of 200–500 sccm, DCPCVD is used to grow the initial diamond layer with a thickness of 500–900 μm on the carbon surface of the silicon carbide transition layer for 5–10 h.
6. The preparation method according to any one of claims 1-3, characterized in that, During the formation of a diamond layer on the carbon facet of the silicon carbide transition layer, the carbon facet of the silicon carbide transition layer and the surface of the diamond layer are bonded together through carbon atom diffusion; the formation of a diamond layer on the carbon facet of the silicon carbide transition layer includes: Under conditions of temperature of 1900–2100℃ and pressure of 0.001–0.03 Pa, the carbon surface of the silicon carbide transition layer is heterogeneously bonded to the surface of the initial diamond layer to obtain a second heterogeneous bonding structure. Wherein, the surface roughness of the initial diamond layer is less than the fourth preset roughness, and the value of the fourth preset roughness ranges from 1 to 5 nm; After heterobonding is completed, the second heterobonded structure is annealed for 20 to 40 hours at an annealing temperature of 1800 to 1900°C and an annealing atmosphere of argon or nitrogen, so that the initial diamond layer is transformed into the diamond layer. The thickness of the diamond layer is 300-500 μm.
7. The preparation method according to claim 6, characterized in that, Before forming the diamond layer, the preparation method further includes: forming a plurality of first microchannels in the form of protrusions or grooves on the carbon surface of the silicon carbide transition layer; And / or, before heterobonding the carbon face of the silicon carbide transition layer to the surface of the initial diamond layer, the preparation method further includes: Multiple second microchannels, either protruding or grooved, are formed on the surface of the initial diamond layer; The first microchannel with a protrusion corresponds to the second microchannel with a groove, so that the first microchannel with a protrusion can be embedded in the second microchannel with a groove; the second microchannel with a protrusion corresponds to the first microchannel with a groove, so that the second microchannel with a protrusion can be embedded in the first microchannel with a groove.
8. The preparation method according to claim 7, characterized in that, The formation of multiple first microchannels in the form of protrusions or grooves on the carbon surface of the silicon carbide transition layer includes: Under conditions of pulse width of 500ps to 1ns, laser power of 10 to 15W, and laser repetition frequency of 20 to 100kHz, laser etching is used to form multiple first microchannels in the carbon surface of the silicon carbide transition layer in the form of protrusions or grooves; or under conditions of etching temperature exceeding 1800℃ and etching gas of CF4, O2, or Ar, plasma etching is used to form multiple first microchannels in the carbon surface of the silicon carbide transition layer in the form of protrusions or grooves. Wherein, the width of the first microchannel is 5-10 μm; and / or, the depth of the first microchannel is 30-50 μm; and / or, the lateral spacing of the first microchannel is 5-10 mm. And / or, the formation of a plurality of second microchannels in the form of protrusions or grooves on the surface of the initial diamond layer includes: Under conditions of pulse width of 500ps to 1ns, laser power of 10 to 15W, and laser repetition frequency of 20 to 100kHz, multiple second microchannels in the shape of protrusions or grooves are formed on the surface of the initial diamond layer by laser etching; or under conditions of etching temperature exceeding 1800℃ and etching gas of CF4, O2, or Ar, multiple second microchannels in the shape of protrusions or grooves are formed on the surface of the initial diamond layer by plasma etching. Wherein, the width of the second microchannel is 5-10 μm; and / or, the depth of the second microchannel is 30-50 μm; and / or, the lateral spacing of the second microchannel is 5-10 mm; And / or, the thickness of the diamond layer is less than or equal to two-thirds of the thickness of the silicon carbide composite seed crystal, and the thickness of the diamond layer is greater than or equal to one-half of the thickness of the silicon carbide composite seed crystal; And / or, the thickness of the silicon carbide seed crystal is less than one-third of the thickness of the silicon carbide composite seed crystal.
9. A silicon carbide composite seed crystal, characterized in that, The silicon carbide composite seed crystal is prepared using the method for preparing silicon carbide composite seed crystal according to any one of claims 1-8.
Citation Information
Patent Citations
Method for optimizing growth of silicon carbide single crystals
CN106435735A